2021
DOI: 10.1186/s12984-021-00923-2
|View full text |Cite
|
Sign up to set email alerts
|

SWADAPT1: assessment of an electric wheelchair-driving robotic module in standardized circuits: a prospective, controlled repeated measure design pilot study

Abstract: Objectives The objective of this study is to highlight the effect of a robotic driver assistance module of powered wheelchair (PWC), using infrared sensors and accessorizing a commercial wheelchair) on the reduction of the number of collisions in standardized circuit in a population with neurological disorders by comparing driving performance with and without assistance. Methods This is a prospective, single-center, controlled, repeated measure des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Three real circuits intended to assess the driving performances with PWC in indoor situations have been defined according to [ 23 , 26 28 ]. The first circuit (C1) is composed of several basic tasks such as driving forwards (10 m) and backwards (2 m), turning in place and while moving forwards (90°).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three real circuits intended to assess the driving performances with PWC in indoor situations have been defined according to [ 23 , 26 28 ]. The first circuit (C1) is composed of several basic tasks such as driving forwards (10 m) and backwards (2 m), turning in place and while moving forwards (90°).…”
Section: Methodsmentioning
confidence: 99%
“…Even though this study does not deal with the use of the simulator for learning to drive, this is the final objective of this device. We proposed to regular PWC users with neurological disorders to test this simulator prototype on a driving task in a 3D virtual environment replicating 3 real standardized driving circuits [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this trial indicate that the proposed assistance solutions are accurate, risk averse, and safe, with a high degree of acceptability. Moreover, even if the participants were already expert drivers, the study has shown that the use of the assistance module statistically significantly reduced the number of collisions during complex maneuvers [6]. The protocol followed during the SWADAPT2 clinical trial was similar to that of SWADAPT1, but 28 users with driving difficulties took part in it.…”
Section: Driving Assistancementioning
confidence: 99%
“…The preferences and priorities have been identified by our clinical partners, and they have been translated into a range of functional requirements and technical specifications (see Figure 1 for an excerpt). On this basis, we have devised five standardized obstacle courses of growing complexity, which have been used during our clinical trials [6]. They cover a fairly large spectrum of maneuvers and real-life situations, such as corridor following, entering and reversing out of an elevator, moving up a slope, descending a curb ramp, and so on.…”
Section: Motivation and Original Contributionsmentioning
confidence: 99%
See 1 more Smart Citation